Outcome parity in low and high-energy Lisfranc injuries: Evaluation of minimally invasive percutaneous plate osteosynthesis - Randolino, Juan Pablo; Gonzalez, Emanuel; Gaitan, Laura; Slullitel, Gaston; Alvarez, Gonzalo; Lopez, Valeria (Journal of the Foot & Ankle, 2025)
Objective: This study aims to present the clinical and radiographic results of a prospective cohort followed for three years, treated with indirect reduction and percutaneous fixation in Lisfranc injuries. Methods: A prospective study of 27 consecutive patients with Lisfranc injury was conducted. Patients underwent percutaneous plate and extraarticular screw fixation. Quality of reduction was classified as anatomical, almost anatomical, and non-anatomical. The AOFAS score was used for clinical evaluation. A statistical analysis was performed. Results: Twenty-seven patients with a mean follow-up of 35.5 months were analyzed. Seventeen sustained high-energy injuries, while ten presented low-energy injuries. The postoperative AOFAS at the final follow-up was 81 points. Patients with a greater number of affected columns, evident instability, or staged procedures had lower AOFAS scores. Global quality of reduction positively correlates with the AOFAS score, although no significant association between the number of affected columns and the quality of reduction was observed. Conclusion: Patients with high-energy injuries achieved good results, with a high percentage of anatomical reductions, without differences compared with low-energy injuries. Level of Evidence; IV Case series